1998
DOI: 10.1016/s0272-6963(98)00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing production and operations management related journals: the European perspective

Abstract: Ž.Following the evolution and growth of the field of production and operations management POM , a number of studies have recently appeared which provide insights on the ranking of the research outlets of the field. These studies are US-based and exclude non-US researchers. In this study we present rankings of the publication outlets in the POM discipline as perceived by POM researchers in Europe. Perceived relevance and quality of POM related journals, and differences between the rankings obtained by our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 16 publications
6
59
1
2
Order By: Relevance
“…They have grown in popularity over the past 10 years, as academics themselves have sought to develop rating and ranking systems as an alternative to lists produced by external agencies. Peer assessment has been used in operations management (Soteriou, Hadjinicola, & Patsia, 1999), MIS (Mylonopoulos & Theoharakis, 2001), construction management (Wing, 1997), international business (Dubois & Reeb, 2000), and tourism and hospitality (Hsu & Yeung, 2003;Pechlaner, Zehrer, Matzler, & Abfalter, 2004;Schmidgall, Woods, & Rutherford, 1996;Sheldon, 1990). The large amount of interest from the tourism community reflects a collective frustration at both having to justify the academic credibility of tourism as a field of study and the failure of other rating systems to include a sufficiently large sample of journals.…”
Section: Peer Assessmentmentioning
confidence: 99%
“…They have grown in popularity over the past 10 years, as academics themselves have sought to develop rating and ranking systems as an alternative to lists produced by external agencies. Peer assessment has been used in operations management (Soteriou, Hadjinicola, & Patsia, 1999), MIS (Mylonopoulos & Theoharakis, 2001), construction management (Wing, 1997), international business (Dubois & Reeb, 2000), and tourism and hospitality (Hsu & Yeung, 2003;Pechlaner, Zehrer, Matzler, & Abfalter, 2004;Schmidgall, Woods, & Rutherford, 1996;Sheldon, 1990). The large amount of interest from the tourism community reflects a collective frustration at both having to justify the academic credibility of tourism as a field of study and the failure of other rating systems to include a sufficiently large sample of journals.…”
Section: Peer Assessmentmentioning
confidence: 99%
“…Studies by Vokurka [34] and Goh et al [12] used objective citation indices measures to classify POM-related journals. Soteriou et al [31] classified POM-related journals in terms of their quality and relevance based on the perceptions of European POM researchers. Barman et al [3] report that the quality and relevance of POM journals, as perceived by US academics, remained constant when compared with the perceptual findings of the Barman et al [4] study, and further comments on the differences between European and US academics, as identified by Soteriou et al [31].…”
mentioning
confidence: 99%
“…Perception-based studies involve consultations with researchers in the field of interest regarding a set of journals based on criteria such as the quality and relevance of these journals [41]. In total, seven perception-based studies were analyzed [42][43][44][45][46][47][48].…”
Section: Methodological Proceduresmentioning
confidence: 99%